Endogenous CRISPR/Cas systems for genome engineering in the acetogens Acetobacterium woodii and Clostridium autoethanogenum - Poulalier-Delavelle, Margaux; Baker, Jonathan P.; Millard, James; Winzer, Klaus; Minton, Nigel P. (Frontiers in Bioengineering and Biotechnology, 2023)
Acetogenic bacteria can play a major role in achieving Net Zero through their ability to convert CO2 into industrially relevant chemicals and fuels. Full exploitation of this potential will be reliant on effective metabolic engineering tools, such as those based on the Streptococcus pyogenes CRISPR/Cas9 system. However, attempts to introduce cas9-containing vectors into Acetobacterium woodii were unsuccessful, most likely as a consequence of Cas9 nuclease toxicity and the presence of a recognition site for an endogenous A. woodii Restriction-Modification (R-M) system in the cas9 gene. As an alternative, this study aims to facilitate exploitation of CRISPR/Cas endogenous systems as genome engineering tools. Accordingly, a Python script was developed to automate the prediction of Protospacer Adjacent Motif (PAM) sequences and used to identify PAM candidates of the A. woodii Type I-B CRISPR/Cas system. The identified PAMs and the native leader sequence were characterised in vivo by interference assay and RT-qPCR, respectively. Expression of synthetic CRISPR arrays, consisting of the native leader sequence, direct repeats, and adequate spacer, along with an editing template for homologous recombination, successfully led to the creation of 300 bp and 354 bp in-frame deletions of pyrE and pheA, respectively. To further validate the method, a 3.2 kb deletion of hsdR1 was also generated as well as the knock-in of the Fluorescence-Activating and Absorption-Shifting Tag (FAST) reporter gene at the pheA locus. Homology arms lengths, cell density, and the amount of DNA used for transformation were found to significantly impact editing efficiencies. The devised workflow was subsequently applied to the Type I-B CRISPR/Cas system of Clostridium autoethanogenum, enabling the generation of a 561 bp in-frame deletion of pyrE with 100% editing efficiency. This is the first report of genome engineering of both A. woodii and C. autoethanogenum using their endogenous CRISPR/Cas systems.